Self-esteem, news media exposure and civic consciousness of urban adolescents from low income families. - Tamam, Ezhar; Ismail, Fadzil Imran (2007)
This research examines the role of self-esteem and exposure to news media on the civic consciousness of early, middle and late adolescents from urban low income families. A total of 397 adolescents from eight residential areas (Projek Perumahan Rakyat) in Kuala Lumpur voluntarily participated in the survey. Self-administered questionnaires were distributed to the respondents in person at their social meeting places. One-way analysis of variance revealed that late adolescents had a significantly higher level of civic consciousness compared to that of the level of early and middle adolescents. The results of regression analysis showed that self-esteem is a significant determinant of civic consciousness. Contrary to expectation, exposure to news and information in the mainstream media was not a significant determinant of civic consciousness of adolescents.